Incidencia de la inclusión educativa en las relaciones interpersonales de los estudiantes de cuarto año de educación general básica paralelos “a” y “b” en la escuela fiscal Abdón Calderón, parroquia Aláquez cantón Latacunga - Chicaiza Taipicaña, Verónica Elizabeth (2015)
This research was realized at “Abdon Calderon” public school, which focuses on processes that provide educative inclusion according the needs have occurred during the education. This research is an important support to reinforce the inclusion and improve the interpersonal relationships in the institution, through socialization about training school life and achieving as results the good living. The research was based on quantitative and qualitative paradigm, by collecting and processing data information obtaining result, which help tom understand, analyze, interpret and relate the educational phenomenon and explain it with belonging, which will improve and give an important change whit all members in the educational community, in this way, it will fortify the good relations between them. The purpose of this research focuses on improving the interpersonal relationships through the socialization of workshops taking as a key element the educative inclusion.